The Role of Association in Early Word-Learning - Johnson, Scott P. (Frontiers in Psychology, 2012)
Word-learning likely involves a multiplicity of components, some domain-general, others domain-specific. Against the background of recent studies that suggest that word-learning is domain-specific, we investigated the associative component of word-learning. Seven- and 14-month-old infants viewed a pair of events in which a monkey or a truck moved back and forth, accompanied by a sung syllable or a tone, matched for pitch. Following habituation, infants were presented with displays in which the visual-auditory pairings were preserved or switched, and looked longer at the “switch” events when exposure time was sufficient to learn the intermodal association. At 7 months, performance on speech and tones conditions was statistically identical; at 14 months, infants had begun to favor speech. Thus, the associative component of word-learning does not appear (in contrast to rule-learning, Marcus et al., 2007) to initially privilege speech.